Effect of Sugar Substitution with Dates Puree (Phoenix dactylifera L.) on the Physical and Organoleptic Characteristics of Kefir Ice Cream (Faculty of Animal Science Universitas Brawijaya, 2021)
The sour taste of kefir ice cream is less attractive with consumers, so it is necessary to add sweeteners. Dates can be used as a natural sweetener in making kefir ice cream. The aims of this research is to determine the effect of sugar substitution with dates puree on overrun, melting rates, viscosity, pH value and organoleptic properties of kefir ice cream. The method used in this research was an experimental with Completely Randomized Design (CRD) with 5 treatments and 4 replications. Overrun, melting rates, viscosity and pH values were analyzed by ANOVA test and followed by Duncan Multiple Range Test, meanwhile organoleptic characteristic were analyzed by Kruskall Wallis test and followed by Mann-Whitney test. The results showed that the substitution of sugar with dates puree as a sweetener had a significant effect (p<0.05) on overrun, melting rates, viscosity and pH value of kefir ice cream. Substitution of sugar with dates puree had a significant effect (p<0.05) on sweetness, sourness, brownish color and softness of kefir ice cream. The sugar substitution with dates puree 25%: 75% (T1) had the best overrun, melting rate as well as the organoleptic characteristic because it was able to reduce the sour taste of kefir ice cream